Quick Reference Wallet Card on Euthanasia of Cattle - Jan K. Shearer; Paul Nicoletti (EDIS)
VM-155, a full-color wallet card by Jan K. Shearer and Paul Nicoletti, describes the correct way to humanely euthanize cattle using gunshot or penetrating captive bolt. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.